Nonlinear graphene quantum capacitors for electro-optics - Sina Khorasani (Nature Portfolio, 2017)
Quantum Technology: Graphene Capacitor Enhances Nonlinear Circuitry at Low Temperatures Graphene capacitors, known to be strongly nonlinear at very low temperatures, now find novel applications in superconducting quantum circuits. A research carried out at Sharif University of Technology, Iran, and École Polytechnique Fédéral de Lausanne, Switzerland, reveals a whole new range of applications for quantum graphene capacitors. This is a three-layer device, made of two graphene layers separated by a two-dimensional dielectric. At reasonably small area, the capacitor exhibits strong nonlinearity leading to unprecedented applications in quantum technology. It could serve as the missing element in the toolbox of low temperature circuits, where nonlinear inductors and Josephson junctions mostly dominate. It also would enable a new and diverse range of quantum circuits, while easily providing access to ultrastrong coupling.